Migration out of poverty: The case of post-war migration in Mozambique - Maimuna Ibraimo; Eva-Maria Egger (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2023)
Internal migration plays an important role in the economic development of individuals, their families, and their country. This study describes Mozambique's most common migration patterns from 1992 until 2017 using data from three population censuses. We focus on the most important moves between regions, provinces, and rural and urban areas. Further, we document the characteristics of migrants to assess selection patterns. In the final step, we estimate the relationship between migration and multidimensional poverty by applying inverse probability weighted regression adjustment (IPWRA). We find that migration in Mozambique was very high, especially between rural areas, after the war ended as people returned from displacement. Still, it is very low in the most recent period. Recently, migration has been the main contributor to the urbanization of the greater Maputo area (capital city). Migrants appear to be positively selected on education, and are, on average, less likely to be poor.
Keywords: I32; O15; O55; R23; 330; migration; Mozambique; poverty; IPWRA